PENGARUH PENERAPAN MANAJEMEN RISIKO BISNIS DALAM SMALL BUSINESS DEVELOPMENT PADA UMKM KEDAI OMMED - Agnes Doraresta Khatarina Tokan; Dewi; Gladys Christiani; Mardiana Ng; Serina; Wirren Chang (Lembaga Pengembangan Kinerja Dosen, 2023)
This risk can come at any time, therefore research and analysis and innovation must be carried out on a business so that it is not left behind or affected by a situation or disaster that occurs suddenly. The type of method used in this research is literature study. Literature study is a method of collecting data by looking for information or references online through articles, journals, websites, and so on. In this study, the authors analyze the risks that occur in UMKM Kedai Ommed, namely technology and inflation. In this study, the authors analyze how to deal with these risks with the 4T hazard response and risk response. Keywords: Risk, Risk Management, MSME.